EVALUASI LIMA JENIS INNER CARRIER DAN FORMULASI BACILLUS SUBTILIS UNTUK PENGENDALIAN HAWAR PELEPAH JAGUNG (RHIZOCTONIA SOLANI KUHN) - Amran Muis; Nurasiah Djaenuddin; Nurnina Nonci (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Evaluation of five inner carriers and Bacillus subtilis formulation to control banded leaf and sheath blight (Rhizoctonia solani Kuhn). One alternative control method against plant pathogens is the use of antagonistic microorganisms, such as Bacillus subtilis. The use of the antagonistic bacteria on corn especially in Indonesia is still lack. The objective of this research was to evaluate some inner carrier and to make formulated antagonistic B. subtilis to be used as biological control agents on corn diseases. This research consists of laboratory and greenhouse activities. The laboratory activities consist of B. subtilis biomass production, formulation of B. subtilis, and evaluation of five types of inner carrier. In the greenhouse, testing the formulation B. subtilis with talc as an inner carrier, which is compared with the treatment solution of B. subtilis, nordox, metalaxyl fungicides. The data collected in this study were percentage of germination, damping off due to pathogen R. solani, plant height, plant fresh weight, and percentages of R. solani incidence on 14 DAP. The results showed that talc powder and corn flour were the best inner carrier to be used in sorage formulation of antagonistic Bacillus. Formulated Bacillus subtilis TM4 showed no negative affect on seed germination and able to suppress the development of R. solani in greenhouse.